Henrich Steffens i 1842 om nordisk mytologi - Lundgreen-Nielsen, Flemming (Universitets-Jubilæets Danske Samfund, 2024)
In 1842 Henrich Steffens (1773-1845) gave two lectures in German on the influence of Christianity on Norse mythology at the Royal Prussian Academy of Sciences in Berlin, which were printed posthumously in 1846. However, instead of sticking to his elected angle Steffens described different tribes of ancient pagan peoples and their languages and cultural levels such as Anglo-Saxons, Picts, Irishmen, Scots and Scandinavians in a Norwegian dominated North Sea and North Atlantic Viking Empire. Seemingly satisfied to recite only a few stanzas of well-known Edda poems (in German), Steffens openly admits that he does not have anything new to say about Norse myths. Though they became quite fashionable in Danish romantic poetry even heralded by Steffens in Copenhagen 1802-04, he knew little about them and did not really care for them. The 1842-lectures of Steffens have never been translated into Danish and are not included in scholarly analyses of his writings. Hence a summary with brief direct quotes and key-words rendered in modern Danish illustrating his main points might be useful.